An exemption from taxation of an income arising from financial instruments hedging foreign exchange risk in business activities conducted on the basis of a decision on support or in a special economic zone on the basis of a permit - Dominika Wróblewska (Prawo Budżetowe Państwa i Samorządu)
This article aims to answer the question whether an income arising from financial instruments hedging foreign exchange risk, i.e. the income from forward contracts and currency options, can be considered as an income from an economic activity conducted on the basis of a Special Economic Zone (SEZ) Permit or an economic activity specified in the decision on support. In the Author’s opinion, the income from contracts for the purchase or sale of foreign currencies constitutes the income from tax-exempt activities, provided that transactions were used to hedge foreign exchange risk related to activities specified in the SEZ Permit or the decision on support. This is a tantamount to the possibility of exempting such an income from corporate income tax. The empirical and analytical method was applied for the purpose of the analysis of legal acts regulating the discussed subject. Literature, individual interpretations of tax law, tax explanations, and judgments of administrative courts were used as well.